Heart rate detection in highly noisy handgrip electrocardiogram - Lin, C.C.; Hu, W.C.; Chen, C.M.; Weng, C.H. (2008 Computers in Cardiology, 2008)
This study is to develop the handgrip heart rate detection methodology based on template matching algorithm. A sixth-order Butterworth bandpass filter with a passband of 1 to 30 Hz was used to filter out baseline shift and noise above 30 Hz including power line noise. The resulting QRS waveform will be processed by the matching filter and ready for heart beat detection. The result of detected heart beat will be processed by a weighting function to further minimize the false heartbeat detection. The performance of heart rate detection algorithm was tested under resting and exercising condition. Five Taiwanese male subjects averaged age of 25 were tested. The experimental results showed that the error rates were 0.78% (total of 766 heart beats) at resting condition and 3.83% (total of 3077 heart beats) during exercise.